Associations of IRAK1 Gene Polymorphisms and mRNA Expression With NMOSD Risk in the Northern Chinese Han Population - Yan, Hongjing; Guo, Ruoyi; Chen, Weifeng; Xi, Xutao; Wang, Lianchang; Ma, Jianxun; Li, Bin (Frontiers in Neurology, 2021)
IRAK1 is a very important immunomodulatory gene for autoimmune diseases located on the X chromosome.However,there was litttle study about the correlation of IRAK1 functional SNPs status with mRNA expression in NMOSD patients.In this study, we aimed to investigate the plausible association between IRAK1 polymorphism,mRNA gene expression of IRAK1, and neuromyelitis optica spectrum disorders (NMOSD) in a northern Chinese Han population.96 patients with NMOSD were recruited and compared to 216 healthy subjects as the control group was genotyped by using the SNaPshot technique and the polymerase chain reaction. Allele, genotype, and haplotype frequencies were compared. Stratified analyses were conducted by age, sex, AQP4 status, age of onset.30 NMOSD patients (of active phase), and15 healthy control subjects were enrolled for the IRAK1 mRNA study.qPCR was used to detected IRAK1 mRNA levels in the peripheral blood mononuclear cells of both groups. Stratified analyses were conducted based on gender and IRAK1 genotype.The results shows frequencies for IRAK1 polymorphisms（rs1059702、rs7061789 、rs1059703和rs3027898） were significantly different between NMOSD cases and controls. The level of IRAK1mRNA was markedly high in NMOSD when compared to healthy control groups(p<0.001). Female patients with GG genotype of rs1059703 had a higher level of IRAK1mRNA compared to those with AG genotypes (P = 0.005) and the male patients with GG genotype(p=0.044).The results indicates IRAK1 polymorphisms were highly correlated with NMOSD susceptibility.IRAK1 mRNA expression was significantly increased in the female NMOSD and was found to be associated with active NMOSD.